Weekly compost extract applications shift plant resource allocation toward defense and suppress Meloidogyne javanica - El Mehdi Bouchtaoui; Ayoub Haouas; Mouna Fahr; Driss Iraqi; Khalid Azim; Abdelfattah A. Dababat; Hasna Yachou; Abdelmjid Zouahri; Abdelaziz Smouni; Fouad Mokrini (Applied Soil Ecology, 2026)

Phosphate sludge-enriched compost for the control of Meloidogyne javanica and improved organic tomato growth - El Mehdi Bouchtaoui; Ayoub Haouas; Ahmed Mahmoudi; Mouna Fahr; Aouatif Benali; Abdelmjid Zouahri; Khalid Azim; Driss Iraqi; Abdelfattah A. Dababat; Mustafa İmren; Abdelaziz Smouni; Fouad Mokrini (Organic Agriculture, 2026)

Quality assessment of poultry manure compost: focus on organic amendment and bioremediation roles toward sustainable agriculture - Rachid Aboutayeb; Saad Fijahi; Lahcen Hssaini; Khalid Azim (Euro-Mediterranean Journal for Environmental Integration, 2025)

Exploring mechanisms of compost-mediated suppression of plant pathogens: A critical review - El Mehdi Bouchtaoui; Ayoub Haouas; Abdelfattah A. Dababat; Rachid Lahlali; Aouatif Benali; Mouna Fahr; Abdelaziz Smouni; Khalid Azim; Zixiu Liu; Ji Li; Fouad Mokrini (Applied Soil Ecology, 2024)

Harnessing compost and vermicompost for sustainable and effective management of plant-parasitic nematodes in agricultural systems: A critical review - El Mehdi Bouchtaoui; Mouna Fahr; Abdelaziz Smouni; Khalid Azim; Rachid Lahlali; Fouad Mokrini (Physiological and Molecular Plant Pathology, 2024)

Optimization of tomato waste composting with integration of organic feedstock - Ilyass TABRIKA; El Hassan Mayad; James N. Furze; Mina Zaafrani; Khalid Azim (Environmental Science and Pollution Research, 2021)

Solid phosphate sludge composted with organic horticultural residues improves the growth of citrus and forest seedlings - Zakaria Baiz; Khalid Azim; Ilyass Tabrika; Younes Abbas; Jamal Ibijbijen; Abdelhak Hamza; Jamila Dahmani; Mohammed Elguilli (Organic Agriculture, 2021)

Innovative, sustainable, and circular agricultural systems for the future - Gerold Rahmann; Khalid Azim; Irena Brányiková; Mahesh Chander; Wahyudi David; Jan Willem Erisman; Daniel Grimm; Andrew Hammermeister; Li Ji; Anja Kuenz; Anne-Kristin Løes; Wan Abd Al Qadr Imad Wan-Mohtar; et al. (Organic Agriculture, 2021)
This special issue presents the outcomes from “ Designing sustainable and circular agricultural systems for the year 2100 ,” the joint scientific workshop of ISOFAR, the Thünen-Institute, and INRA-Morocco, which was held from November 14 to 16, 2019 in Marrakesh, Morocco. Nineteen scientists from a broad array of background and nationalities came together with the understanding that food security globally is at risk, especially in the post-2050 timeframe. Current concepts, strategies, measures, and scientific efforts carried out by governments, NGOs, businesses, and societies do not deliver satisfying solutions for how to sustainably produce enough healthy and affordable food to support the global population. With the economic and social impact of the Covid-19 pandemic in 2020, it became even more evident that food security is a challenge. This workshop took an innovative approach to addressing the challenges of future agriculture by considering sustainable, circular agricultural systems. Participants presented research results on algae-based food, edible insects, mushrooms, novel concepts for nutrient management, bioreactor-based farming, sustainable food culture, as well as sensor- and remote-controlled automatic food production. This special issue presents the papers contributed to the workshop and the results of the discussions.

Optimization of solid phosphate sludge composting by integration of horticultural waste - Ilyass Tabrika; El Hassan Mayad; Mina Zaafrani; Mohammed El Guilli; Khalid Azim (Organic Agriculture, 2021)

From its roots, organic inspires science, and vice-versa: science forum of the Organic World Congress 2020 in Rennes, France - Gerold Rahmann; Khalid Azim; Mohammad Reza Ardakani; Veronique Chable; Felix Heckendorn; Paola Migliorini; Bram Moeskops; Daniel Neuhoff; Frederic Rey; Ewa Rembiałkowska; Jessica Shade; Marc Tchamitchian (Organic Agriculture, 2020)

Composting of tomato plant residues: improvement of composting process and compost quality by integration of sheep manure - Ilyass Tabrika; Khalid Azim; El Hassan Mayad; Mina Zaafrani (Organic Agriculture, 2020)

Elucidation of functional chemical groups responsible of compost phytotoxicity using solid-state 13C NMR spectroscopy under different initial C/N ratios - Khalid Azim; Youssef Faissal; Brahim Soudi; Claude Perissol; Sevastianos Roussos; Imane Thami Alami (Environmental Science and Pollution Research, 2018)